Dynamics of the 1057 M 6 earthquake rupture and seismic hazard implications for the Beijing region, China - Xie, Zhangdi (Frontiers in Earth Science, 2025)
Seismic activity frequently occurs in the North China Plain seismic belt. Historical earthquake records for the fault southwest of Beijing are sparse, with only one significant event: the 1057 M 6 earthquake. This study focuses on the southern extension of the Nanyuan-Tongxian Fault. Using dynamic numerical methods, we simulate the rupture process of this earthquake to investigate its impact on strong ground motions in Beijing and surrounding areas. First, on the basis of the fault geometry and hydraulic fracturing stress data, we set the dynamic parameters of the fault plane and construct a curved fault model. Numerical simulation of the dynamic rupture process yielded the following results: a maximum slip of 0.75 m, an average slip of 0.49 m, a rupture duration of approximately 10 s, and a moment magnitude (Mw) of 6.5. The rupture propagated bilaterally; influenced by fault geometric bending, the peak slip rate reached 0.7 m/s on the SW side, whereas the slip rate on the NE side was smoother. The strong ground motion distribution showed a maximum intensity of VIII, which was concentrated along the fault trace with a significant hanging wall effect. Notably, owing to the combined effects of rupture directivity and fault bending, anomalously high-intensity zones appeared in areas distant from the epicenter, such as Shunyi and Tongzhou. This pattern differs significantly from the historical seismic impact pattern of the Sanhe-Pinggu Fault on the northeastern side. Further simulations of the epicenter within the fault indicate that if a future earthquake’s epicenter is located west of the fault center, Tongzhou would still face high-intensity ground motion risks. The results from both planar-fault and 3-D velocity-model simulations further demonstrate that strong ground-motion characteristics are influenced by multiple factors. This study reveals the unique seismogenic mechanism of the Nanyuan-Tongxian Fault, providing a key basis for seismic hazard assessment southwest of Beijing.